If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -81 + -9x = 21 + 8x Solving -81 + -9x = 21 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -81 + -9x + -8x = 21 + 8x + -8x Combine like terms: -9x + -8x = -17x -81 + -17x = 21 + 8x + -8x Combine like terms: 8x + -8x = 0 -81 + -17x = 21 + 0 -81 + -17x = 21 Add '81' to each side of the equation. -81 + 81 + -17x = 21 + 81 Combine like terms: -81 + 81 = 0 0 + -17x = 21 + 81 -17x = 21 + 81 Combine like terms: 21 + 81 = 102 -17x = 102 Divide each side by '-17'. x = -6 Simplifying x = -6
| 10r-15s= | | 12n+3=4n-6 | | 9x^2-79x-130=0 | | 14c+28d= | | 7y+6x-3=3y-3x+2 | | n+(-20)=7-n | | 84-3x=3x+24 | | 4y+6z= | | 35-3x=2x | | 61-3x=61-3x | | 8n+24= | | 5e-5f= | | 3a-3b= | | 79-3x=2x-9 | | 12x-2=7x | | 4x^2+ab-2ax-2bx=0 | | y=5x^2-30x+20 | | (X+2)(x-4)=16 | | (4w+8)/(w^2-4w)(w^2-3w-4)/(w^2-3w+2)=0 | | 20a^3-39a^2+18a=0 | | 59-4x=10x-17 | | 6d+1=4d+7 | | 9(a+9)=104.4 | | 6x(x-5)=0 | | (5x-8)(4x-9)= | | 3x+59=8x-6 | | h=32+-16t^2 | | 2(3)-5(-4)=-10 | | 18(2m+11)= | | 13.4=3c-7 | | 4e-6=12 | | 11x+7y=180 |